Novel method of dual fiber Bragg gratings integrated in fiber ring laser for biochemical sensors. (26th March 2018) - Bui, H; Pham, T B; Nguyen, V A; Pham, V D; Do, T C; Nguyen, T V; Hoang, T H C; Le, H T; Pham, V H
Abstract: Optical sensors have been shown to be very effective for measuring the toxic content in liquid and air environments. Optical sensors, which operate based on the wavelength shift of the optical signals, require an expensive spectrometer. In this paper, we propose a new configuration of the optical sensor device for measuring wavelength shift without using a spectrometer. This configuration has a large potential for application in biochemical sensing techniques, and comes with a low cost. This configuration uses dual fiber Bragg gratings (FBGs) integrated in a fiber ring laser structure of erbium-doped fiber, in which one FBG is used as a reference to sweep over the applicable spectrum of the etched-Bragg grating. The etched-FBG as a sensing probe is suitable for bio- and/or chemical sensors. The sensitivity and accuracy of the sensor system can be improved by the narrow linewidth of emission spectra from the laser, the best limit of detection of this sensor is 1.5 × 10 −4 RIU (RIU: refractive index unit), as achieved by the optical sensor using a high resolution spectrometer. This sensor system has been experimentally investigated to detect different types of organic compounds, gasoline, mixing ratios of organic solvents in gasoline, and nitrate concentration in water samples. The experimental results show that this sensing method could determine different mixing ratios of organic solvents with good repeatability, high accuracy, and rapid response: e.g. for ethanol and/or methanol in gasoline RON 92 (RON: research octane number) of 0%–14% v/v, and nitrate in water samples at a low concentration range of 0–50 ppm. These results suggest that the proposed configuration can construct low-cost and accurate biochemical sensors.